The Sources of the Union Wage Gap: The Role of Worker, Firm, Match, and Jobtitle Heterogeneity - John T. Addison; Pedro Portugal; Hugo Vilares (Center for Economic Studies and ifo Institute (CESifo), 2018)
Using matched employer-employee-contract data for Portugal – a country with near-universal union coverage – we find evidence of a sizable effect of union affiliation on wages. Gelbach's (2016) decomposition procedure is next deployed to ascertain the contributions of worker, firm, match, and job-title heterogeneity to the union wage gap. Of these the most important is the firm fixed effect, followed at some distance by union workers gaining from elevated job titles and/or more generous promotion policies. For its part, unobserved worker quality plays only a very weak role, while there is even less suggestion that improved match quality bolsters the union premium.
Keywords: J31; J33; J41; J51; J52; 330; union density; union wage gap; worker/form/job-title fixed effects; match quality; Gelbach decomposition; Portugal